Precise of The Laws of Armed Conflicts - PPKE-JÁK (PPKE-JÁK; Mitró Tamás, 2006)
Dr. Juris, Captain (Retired) Luis-Philippe F. Rouillard Precise of The Laws of Armed Conflicts című doktori értekezésének kutatóhelyi vitája. :